REGULASI DIRI DENGAN IMPULSIVE BUYING TERHADAP PENGGUNA E-COMMERCE PADA MAHASISWA SURABAYA: SELF-REGULATION WITH IMPULSIVE BUYING TOWARDS E-COMMERCE USERS IN SURABAYA STUDENT - Ramadhan, Ayu Lisdianti; Santi, Dwi Rukma; Jainuddin, Jainuddin (Jurnal Psikologi Jambi, 2024)
ABSTRACT Introduction Impulsive buying is consumer behavior in buying goods in large quantities without careful planning and consideration. Self regulation plays an important role in shaping the behavior of individuals who are able to control their actions and be responsible for all the decisions they make. Individuals who have self-regulation tend to have good control over their impulsive buying. Objective This research aims to examine the relationship between self-regulation and impulsive buying behavior among e-commerce users among students in Surabaya. Method This research uses a quantitative approach with simple random sampling techniques. This sample consisted of 80 Surabaya students. The measuring instruments used in this research used the Self-Regulation Questionnaire (SRQ) and Impulsive Buying Tendency (IBT) scales. Result Data analysis used chi-square with the correlation value obtained at p = -0.007 (p < 0.05), which means there is no significant relationship between self-regulation and impulsive buying behavior in Surabaya students. Conclusion This shows that there is no significant relationship between self-regulation and impulsive buying behavior among Surabaya students. Keywords: Self-Regulation, Impulsive Buying, Surabaya Students ABSTRAKPendahuluan Impulsive buying merupakan perilaku kosumen dalam membeli barang dengan jumlah yang banyak tanpa melakukan perencanaan dan pertimbangan secara matang. Regulasi diri berperan penting dalam membentuk perilaku individu yang mampu mengendalikan tindakan mereka dan bertanggung jawab atas segala keputusan yang mereka buat. Individu yang memiliki regulasi diri cenderung memiliki kontrol yang baik atas impulsive buying. Tujuan Penelitian ini bertujuan untuk menguji hubungan antara regulasi diri dan perilaku impulsive buying terhadap pengguna e commerce pada mahasiswa di Surabaya. Metode Penelitian ini menggunakan pendekatan kuantitatif dengan teknik simple random sampling. Sampel ini terdiri dari 80 mahasiswa Surabaya. Alat ukur yang digunakan dalam penelitian ini menggunakan skala Self-Regulation Questionnaire (SRQ) dan Impulsive Buying Tendency (IBT). Hasil Analisis data menggunakan chi-square dengan nilai korelasi yang diperoleh p = -0,007 (p < 0,05) yang berarti tidak terdapat hubungan yang signifikan antara regulasi diri dengan perilaku impulsive buying pada mahasiswa Surabaya. Kesimpulan Hal tersebut menunjukkan bahwa tidak terdapat hubungan yang signifikan antara regulasi diri dengan perilaku impulsive buying pada mahasiswa Surabaya. Kata Kunci: Regulasi Diri, Impulsif Buying, Mahasiswa Surabaya